Cost of ownership assessment for a da Vinci robot based on US real‐world data. Issue 5 (15th July 2019) - Feldstein, Josh; Schwander, Bjoern; Roberts, Mark; Coussons, Herbert
Abstract: Background: Despite growth of robotic surgery, published literature lacks assessment of the cost of ownership (CoO) of a da Vinci robot by surgical service line and the associated benefit such data provides. Methods: Based on real‐world data (RWD) from 14 US hospitals and ≈6000 da Vinci robotic cases, CoO was assessed using all relevant fixed and variable cost components, calculated by surgical service line. Results: At a representative hospital with an efficient robotic program (n = 424 cases), the weighted average fixed cost per case was $984. Weighted average variable cost per case was $8025 (range: $3325 for Cholecystectomy—multiport, to $16 986 for Rectal Resection). Assessing weighted average by case, main variable cost drivers were non‐da Vinci supplies (49.5%), staff costs (28.6%), and da Vinci supplies (21.9%). Conclusions: Case mix, annual robotic case volumes, and cut‐to‐close/patient‐in‐room time by surgical service line represent core variables influencing robotic program CoO, which help drive profitable program management.